Diagnostic review of the Sphaeropthalmini (Hymenoptera: Mutillidae) of Central and North America, Part 1: minor nocturnal genera - Williams, Kevin A.; Pitts, James P.; Parikh, Grishma R.; Cambra, Roberto A.; Zhang, Yunfan; Bartholomay, Pedro R. (Zootaxa, 2025)
In Part 1 of this diagnostic review on the tribe Sphaeropthalmini in North America (Hymenoptera: Mutillidae: Sphaeropthalminae), we treat the minor nocturnal genera: Acanthophotopsis Schuster, 1958 (six species); Acrophotopsis Schuster, 1958 (six species); Dilophotopsis Schuster, 1958 (three species); Laminatilla Pitts, 2007 (three species); and Schusterphotopsis Pitts, 2003 (one species). The previously unrecognized females are described for three genera (Acanthophotopsis, Laminatilla, and Schusterphotopsis) and nine species (Acanthophotopsis bequaertii Schuster, 1958; Acanthophotopsis dorophora Schuster, 1958; Acanthophotopsis falciformis Schuster, 1958; Acrophotopsis bergi Casal, 1967; Acrophotopsis mickeli Pitts, 2002; Dilophotopsis paron (Cameron, 1896); Laminatilla bicornigera (Schuster, 1958), Laminatilla lamellifera (Schuster, 1958) and Schusterphotopsis barghesti Pitts, 2003). Two new species are described: Acrophotopsis paratropicalis Williams, sp. nov. and Acrophotopsis pumasunam Williams, sp. nov. One new combination is presented: Acanthophotopsis virguncula (Blake, 1886), comb. nov. (transfered from Sphaerophthalma Blake, 1871). Two new synonymies are presented: Stethophotopsis cremauranti Pitts & Manley, 2002, syn. nov. underAcanthophotopsis bequaertii Schuster, 1958) and Acanthophotopsis bifurca Schuster, 1958, syn. nov. under=Sphaerophthalma [sic] virguncula Blake, 1886). Additional comments are also presented regarding the distribution, behavior, and relations of Stethophotopsis maculata Pitts, 2000. New keys to the North American genera of Sphaeropthalmini and keys to species in each of the treated genera are provided.